Effect of ethanolic extract of sambiloto (Andrographis paniculata (Burm.f.) Nees) herbs on adult male mice permatogenesis and the thin layer chromatographic qualitative test - V.S. Halim; C.J. Soegihardjo; D.M. Rizal (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Ethanolic extract of sambiloto (Andrographis paniculata (Burm.f.) Nees) herb was often found in traditional medicine. However, the safety of the extract on man, especially related to the fertility was needed to investigate.For reaching the aim, the extract was administered to adult male DDI mice at three dose levels 11,25mg; 22,5mg, and 45mg/30g BW for 48 days. Effects on fertility were analyzed by histopathological evaluation of the tubulus seminiferous and the results were compared to Cisplatin as positive control for cytotoxic action, as well as to the negative control group. The results showed the damage of spermatogenesis in tubulus seminiferous, degradation and spreading of spermatogenic cells (spermatogonium, primary spermatocytes, secondary spermatocytes, spermatid, spermatozoa), also the damage of Sertoli cell, lyses of lamina basalis and interstitial layer, and Leydig cells appeared intact. The damages showed that ethanolic extract of the herbs could affect spermatogenesis by cytotoxic and antimitotic activities. The damage of tubulus seminiferous at high dose may be irreversible.Thin layer chromatography result showed at least four spot of terpenoid compounds may be andrographolides. The ethanolic extract was more potential than isolate of andrographolide on destroying spermatogenesis tissues.Key words: sambiloto herbs, Andrographis paniculata, andrographolides, spermatogenesis, tubulus seminiferous.